Is neurocysticercosis a risk factor in coexistent intracranial disease? An MRI based study. Issue 3 (1st March 2003) - Azad, R; Gupta, R K; Kumar, S; Pandey, C M; Prasad, K N; Husain, N; Husain, M
Abstract : Background: Previous reports have suggested that neurocysticercosis is associated with glioma and Japanese encephalitis, and that it is a risk factor for stroke. Objective: To determine if neurocysticercosis has a significant association with, or is a risk factor for, coexistent pathologies such as Japanese encephalitis, glioma, abscess, tuberculoma, or infarction. Subjects: 10 350 patients from the hospital population who underwent 1.5 T cranial magnetic resonance imaging during the previous 12 years were evaluated for the presence of neurocysticercosis and coexisting pathology. Design: Retrospective cohort analysis. Results: The prevalence of neurocysticercosis in cases with dual pathology was significantly less than in a control group (1.1% v 8.3%; z = 11.05; p < 0.001, power of test = 1). Neurocysticercosis lesions were less common (p < 0.05) in the different subgroups of coexistent pathology than in the control group except in the case of Japanese encephalitis, where the difference was non-significant (z = 0.69, p = 0.49). The relative risk was less than 1 in all subgroups except Japanese encephalitis, where it was 1.23. The location of neurocysticercosis lesions and the presence of perilesional oedema did not affect coexistent lesion location or severity on a particular side (p = 0.413 and 0.623 for location and perilesional oedema, respectively). When the above factors were analysed separately in patients with Japanese encephalitis, they also did not affect coexistent lesion location or severity (p = 0.659 and 0.548, respectively). Conclusions: The coexistence of neurocysticercosis and other lesions may be an incidental observation in a few patients referred from areas of high prevalence and endemicity. It appears unlikely that neurocysticercosis is a risk factor for other intracerebral pathology. The location of neurocysticercosis lesions and whether or not there is surrounding perilesional oedema do not appear to affect the location or severity of coexisting lesions.